Extracellular vesicles of Trypanosoma cruzi and immune complexes they form with sialylated and non-sialylated IgGs increase small peritoneal macrophage subpopulation and elicit different cytokines profiles - Cornet Gomez, Alberto (2023)
American trypanosomiasis, or Chagas disease, is caused by the protozoan parasite Trypanosoma cruzi and is characterized by the presence of cardiac or gastrointestinal symptoms in a large number of patients during the chronic phase of the disease. Although the origin of the symptoms is not clear, several mechanisms have been described involving factors related to T. cruzi and the host immune response. In this sense, the extracellular vesicles (EVs) secreted by the parasite and the immune complexes (ICs) formed after their recognition by host IgGs (EVs-IgGs) may play an important role in the immune response during infection. The aim of the present work is to elucidate the modulation of the immune response exerted by EVs and the ICs they form by analyzing the variation in the subpopulations of small and large peritoneal macrophages after intraperitoneal inoculation in mice and to evaluate the role of the sialylation of the host IgGs in this immunomodulation. Both macrophage subpopulations were purified and subjected to cytokine expression analysis by RT-qPCR. The results showed an increase in the small peritoneal macrophage subpopulation after intraperitoneal injection of parasite EVs, but a greater increase in this subpopulation was observed when sialylated and non-sialylated ICs were injected, which was similar to inoculation with the trypomastigote stage of the parasite. The cytokine expression results showed the ability of both subpopulations to express inflammatory and non-inflammatory cytokines. These results suggest the role of free EVs in the acute phase of the disease and the possible role of immune complexes in the immune response in the chronic phase of the disease, when the levels of antibodies against the parasite allow the formation of immune complexes. The differential expression of interleukins showed after the inoculation of immune complexes formed with sialylated and non-sialylated IgGs and the interleukins expression induced by EVs, demonstrates that the IgG glycosilation is involved in the type of immune response that dominates in each of the phases of the Chagas disease.